Incorporating strategic petroleum reserve and welfare losses: A way forward for the policy development of crude oil resources in South Asia. (December 2021) - Liu, Zhen; Tang, Yuk Ming; Chau, Ka Yin; Chien, Fengsheng; Iqbal, Wasim; Sadiq, Muhammad
Abstract: South Asia countries are faced with exogenous shocks in addition to energy prices volatility explicitly impacting their socioeconomic advancement as net energy importation countries. As a result, this analysis examines the correlation amongst strategic petroleum reserves (SPR) plus welfare net losses for South Asian economies. Hydrocarbons supply drastically exacerbates energy security concerns beyond welfare net losses regarding the interruption of supply surety. Thus, on this research piece, crude oil distribution security is estimated with respect to the crude volatility index of the South Asian countries, which makes up 84% of global crude imports as well as we approximated safety losses owing to crude distribution interruptions. Inferring from the composite indicator results, Afghanistan is a greatly vulnerable nation concerning energy strategic reserves, whereas India attains minimal vulnerability within the South Asian sub-region. From the analysis, it was discovered that a 30 percent shortfall in crude distribution is accountable for the maximum vacillated composition of crude costing, which rapidly expands the forecasted welfare losses via forty percent cuts in the GDP, that is about seven hundred dollars in South East Asia likewise nine hundred dollars the crude most consuming nations. Our analysis mooted that South Asia countries ought to sustain minimal 90-day reserves commitment, to fight substantial global hydrocarbons supply interruptions, that have effects on price volatility as well as on their socio-economic livelihoods. Highlights: Investigates strategic petroleum reserve and welfare losses for South Asia. Common to these perspectives is examining exposure to supply disruption, but not its probability of occurrence. As oil markets disruptions are rare, we examine the short-term economic security from a fresh perspective.